ナンキョク エンガン イキ ショウワ キチ デノ スイチョク レーダー ヲ モチイタ コウスイリョウ ノ ケンキュウ - 和田, 誠; ワダ, マコト; 小西, 啓之; コニシ, ヒロユキ; Wada, Makoto; Konishi, Hiroyuki (1992)
P(論文) 1987年から始まった「南極域の気候変動に関する総合研究」計画の中で, 雲降水の観測用として1988年に昭和基地に新しい垂直レーダーを設置した。このレーダー観測から1988年の降水量は, 1989年の降水量の約半分であることが見積もられた。1988年2月23日から1989年2月22日までの1年間の降水量は, 約200mm, 1989年2月1日から1989年11月30日までの降水量は約390mmであった。毎年の昭和基地の海氷上の最大積雪深の観測データ, 昭和基地に近い大陸上の旅行ルート沿いの年積雪量のデータも1988年は非常に小さい値を示していた。1988,1989年の降水量の季節変動データ, マラジョージナヤ基地のデータなどから判断すると, 1988年の昭和基地の降水量が非常に少なかった理由は, 秋ではなく, 冬と春の降水量が平年に比べて少なかったことにあると考えられる。 A new vertical pointing radar was installed at Syowa Station in 1988 for observing precipitation and clouds in Antarctic Climate Research project started in 1987. The precipitation of 1988 was approximately half of that of 1989. The total precipitation was estimated at about 200mm from 23 February 1988 to 22 February 1989 and about 390mm from 1 February 1989 to 30 November 1989. The tendency of little snow accumulation in 1988 can be seen in the year-to-year data of the maximum snow depth measured on the sea ice near Syowa Station and in the annual data of snow accumulation around the coastal area of the continent near Syowa Station. The small precipitation of 1988 at Syowa Station seems to be mainly due to small precipitation in winter and spring of 1988,compared with that of 1989. departmental bulletin paper